(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study validates the Boundary Element Method (BEM) solver Capytaine [1] using experimental data from the SWELL (Standardized Wave Energy Converter Array Learning Library) dataset [2], focusing on a single-body (WaveStar-type) configuration under various regular and irregular wave conditions. The literature lacks comprehensive validation of Capytaine’s predictions against experimental data. This work addresses this gap by assessing Capytaine’s ability to predict hydrodynamic coefficients and wave excitation forces, providing a foundation for future applications of the code. Capytaine is used to compute hydrodynamic coefficients, including added mass, radiation damping, and wave excitation forces. A convergence analysis is performed to evaluate the impact of mesh refinement on numerical accuracy, ensuring that results are independent of geometry discretisation. The optimal balance between computational efficiency and precision is identified. The wave excitation forces are further analysed in the time domain using WEC-Sim [3], an open-source simulation tool that calculates the time-varying response of floating bodies. The numerical results of the free surface elevation and wave excitation force are validated against experimental measurements, comparing amplitude and phase to assess Capytaine’s ability to capture the response of the floater. Discrepancies between numerical and experimental results are analysed, addressing the limitations of linear theory and potential errors in experimental data. This work establishes Capytaine as a reliable tool for single-body hydrodynamic analysis and provides a framework for the systematic validation of numerical models against experimental data. These findings support the broader adoption of Capytaine in Wave Energy Converter (WEC) design and optimization. [1] M. Ancellin and F. Dias, “Capytaine: a Python-based linear potential flow solver,” J Open Source Softw, vol. 4, no. 36, p. 1341, Apr. 2019, doi: 10.21105/joss.01341. [2] N. Faedo, Y. Peña-Sanchez, E. Pasta, G. Papini, F. D. Mosquera, and F. Ferri, “SWELL: An open-access experimental dataset for arrays of wave energy conversion systems,” Renew Energy, vol. 212, pp. 699–716, Aug. 2023, doi: 10.1016/j.renene.2023.05.069. [3] D. Ogden et al., “Review of WEC-Sim development and applications,” International Marine Energy Journal, vol. 5, no. 3, pp. 293–303, Dec. 2022, doi: 10.36688/imej.5.293-303.